Ushul Fiqh Sebagai Kerangka Berpikir Dalam Istinbath Hukum Ekonomi Islam - Moh. Romli (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
Studying the science of ushul fiqh in the traditions of Islamic campuses and pesantren is significant for the discovery and formation of Islamic economic law. Even ushul fiqh was made a compulsory subject that must be mastered by Islamic economic law experts today. However, studying ushul fiqh on campus and Islamic boarding schools is trapped in a conservative paradigm, where studying ushul fiqh is limited to something that is consumptive, read and memorized, without contextualization and application. In fact, ushul fiqh must be presented in the midst of Islamic economic in a logical and realistic way, even ushul fiqh as the primary commodity of Muslim economic law experts in the methodology of istinbat al-hukm must touch the economic problems faced by contemporary society. That is the challenge of Islamic economics law experts in studying ushul fiqh today. This paper, how to explain the activities of Muslim economic law experts in studying and understanding ushul fiqh with a descriptive-qualitative research approach model. So what is studied in this paper is the paradigm of thinking in a community of Muslim economists in studying and developing ushul fiqh, when faced with socio-economic problems that require the juridists of Islamic law in the frame of religious texts. From the results of this discussion it can be seen that the ushul fiqh for Islamic economic jurists in the development and dynamics model of ushul fiqh is centered on; revitalization of ushul fiqh, text diversification (fahm nushus asy-shari'ah) and extensification of maqashid as-shari'ah, namely expansion in understanding the purpose of sharia (fahm maqashid as-shari'ah). Besides that, Islamic economic law experts can use the method of ushul fiqh as tariqatu al a'mal, (work patterns), first, making maslahah as a tool in establishing Islamic economic law. Second, it is like matching the fatwa of ulama's law, with the current situation and condition. Third, carry out the operation of Usul Fikih in the formation Islamic economic law as a deductive method. And fourth, complete with Qawaid al-Fiqhiyyah.